The effect of an intraoperative patient-specific, surgery-specific haemodynamic algorithm in improving textbook outcomes for hepatobiliary–pancreatic surgery: a multicentre retrospective study - Carp, Bradly; Weinberg, Laurence; Fletcher, Luke R.; Hinton, Jake V.; Cohen, Adam; Slifirski, Hugh; Le, Peter; Woodford, Stephen; Tosif, Shervin; Liu, David; Muralidharan, Vijaragavan; Perini, Marcos V.; et al. (Frontiers in Surgery, 2024)
The concept of a 'textbook outcome' is emerging as a metric for ideal surgical outcomes. We aimed to evaluate the impact of an advanced haemodynamic monitoring algorithm on achieving a textbook outcome in patients undergoing hepatobiliary-pancreatic surgery.This retrospective, multicentre observational study was conducted across private and public teaching sectors in Victoria, Australia. We studied patients managed by a patientspecific, surgery-specific haemodynamic algorithm or via usual care. The primary outcome was the effect of using a patient-specific, surgery-specific AHDM algorithm on achieving a textbook outcome, with adjustment using propensity score matching. The textbook outcome criteria were defined according to the International Expert Delphi Consensus on Defining Textbook Outcome in Liver Surgery and Nationwide Analysis of a Novel Quality Measure in Pancreatic Surgery.Of the 780 weighted cases, 477 (61.2%, 95% CI: 57.7% to 64.6%) achieved the textbook outcome. Patients in the AHDM group had a higher rate of textbook outcomes (n = 259 [67.8%]) than those in the Usual care group (n = 218 [54.8%]; p <0.001, estimated odds ratio (95% CI) 1.74 (1.30 to 2.33). The AHDM group had a lower rate of surgery-specific complications, severe complications, and a shorter hospital LOS (OR 2.34 [95% CI: 1.30 to 4.21], 1.79 [95% CI: 1.12 to 2.85] and 1.83 [95% CI: 1.35 to 2.46], respectively). There was no significant difference between the groups for hospital readmission and mortality.Conclusions: AHDM use was associated with improved outcomes, supporting its integration in hepatobiliary-pancreatic surgery. Prospective trials are warranted to further evaluate impact of this advanced haemodynamic monitoring algorithm on achieving a textbook impact on long-term outcomes.